Analytical strategy for detecting doping agents in hair - Thieme, D.; Grosse, J.; Sachs, H.; Müller, R. K. (Forensic Science International, 2000)
Lists of banned classes of doping agents are released by the International Olympic Committee, adopted by other sports authorities and updated regularly, including the substance classes stimulants, narcotics, diuretics, anabolic agents, peptide hormones, beta-blockers etc. There are different classes of restriction: anabolic and masking agents (anabolic steroids, diuretics etc.) are always banned for athletes regardless of their topical activity (training or competition) several substances are permitted with certain restrictions (caffeine below a cut-off value, or inhalation of some beta 2 agonists) beta-blockers are prohibited in competitions of certain sports disciplines the majority of the substances (stimulants, narcotics etc.) is prohibited during competitions, so that they do not have to be analysed in out-of-competition samples. A differentiation between training and competition period is impossible by means of hair analysis due to the uncertainty of (especially short-term) kinetic considerations related to hair growth. Therefore, the analytical identification of doping relevant substances in hair is not always a sufficient criterion for a doping offence and the identification of stimulants, beta-blockers etc. in hair would be entirely irrelevant. The most interesting target substances are certainly the anabolic agents, because their desired action (enhanced muscle strength) lasts longer than the excretion, leading to sophisticated procedures to circumvent positive analytical results in competition control. Besides the analysis of out-of-competition control samples, the long term detection of steroids in hair could provide complementary information. An analytical approach to the identification of exogenous steroids in hair requires consideration of the presence of many other steroids in the hair matrix interfering the analysis at trace levels, and of a limited chemical stability. The analysis of endogenous steroids in hair appears to be even more complicated, because the possibility of many biotransformation reactions from (into) other precursors (metabolites) has to be taken into account. Precursor substances of anabolic steroids (especially esters as application forms) are very promising analytical targets of hair analysis, because they can only be detected after an exogenous intake. The quantitative evaluation of active parent compounds like testosterone (which is actively involved in physiological processes of hair growth) in hair is still controversial. Clinical applications under reproducible conditions can be useful, but the biovariability of these parameters will probably prevent the definition of acceptable cut-off levels as a criterion of abuse.